Bionanocomposite MIL-100(Fe)/Cellulose as a high-performance adsorbent for the adsorption of methylene blue - Shahla Abbasi; Zahra Nezafat; Shahrzad Javanshir; Behzad Aghabarari (Scientific Reports)
Abstract World production of dyes is estimated at more than 800,000 t·yr−1. The purpose of this research falls within the scope of the choice of an effective, local, and inexpensive adsorbent to remove dyes from wastewater. Adsorptive elimination of dyes by commonly accessible adsorbents is inefficient. The metal–organic frameworks (MOFs) are an important class of porous materials offering exceptional properties as adsorbents by improving separation efficiency compared to existing commercial adsorbents. However, its powder form limits its applications. One way to overcome this problem is to trap them in a flexible matrix to form a hierarchical porous composite. Therefore, in this work, we prepared MIL-100 (Fe) embedded in a cellulose matrix named MIL-100(Fe)/Cell, and used it as an adsorbent of methylene blue (MB) dye. According to the BET analysis, the specific surface area of the synthesized MOF is 294 m2/g which is related to the presence of the cellulose as efficient and green support. The structure of this composite is approximately hexagonal. Adsorption was studied as a function of contact time, adsorbent mass and pollutant load (concentration), and pH, and the effect of each of them on absorption efficiency was optimized. The MIL-100(Fe)/Cell was capable of removing 98.94% of MB dye with an initial concentration of 150 mg/L within 10 min at pH = 6.5 and room temperature. The obtained maximum adsorption capacity was 384.615 mg/g. The adsorption isotherm is consistent with the Langmuir models. The mechanism of MB adsorption proceeds through п-п and electrostatic interactions.